Case report: Is exchange transfusion a possible treatment for metabolic decompensation in neonates with methylmalonic aciduria in the setting of limited resources? - Xiaoyu Cui; Xiaoyu Cui; Na Li; Hong Xue; Fang Zhang; Jianbo Shu; Jianbo Shu; Yang Liu (Frontiers Media S.A., 2022)
Hyperammonemia is a serious complication of methylmalonic acidemia, with high mortality and permanent neurological sequelae in survivors. Primary hospitals are often the first admission hospitals for these children but are limited by their experience and facilities to provide rapid and effective treatment, increasing the risk of death in children with methylmalonic acidemia's metabolic crisis. In this report, we reported a case of a 7-day-old male neonate with decompensated methylmalonic acidemia, who underwent automatic peripheral arteriovenous exchange transfusion. The serum ammonia level of the boy decreased significantly post exchange transfusion. Therefore, we put forward the suggestion of exchange transfusion for hyperammonemia, in combination with medical therapy, in children with inborn errors of metabolism as an initial treatment option in primary hospitals if a rapid transfer to a center with dialysis facilities is not possible.